2009
DOI: 10.1186/1756-6606-2-27
|View full text |Cite
|
Sign up to set email alerts
|

Multiple functions of precursor BDNF to CNS neurons: negative regulation of neurite growth, spine formation and cell survival

Abstract: Background: Proneurotrophins and mature neurotrophins elicit opposite effects via the p75 neurotrophin receptor (p75 NTR ) and Trk tyrosine kinase receptors, respectively; however the molecular roles of proneurotrophins in the CNS are not fully understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
156
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(164 citation statements)
references
References 58 publications
6
156
1
1
Order By: Relevance
“…ProBDNF can also inhibit neurite outgrowth and reduce spine density (Koshimizu et al 2009). In contrast, mBDNF activates the high affinity receptor, TrkB, which promotes neuronal survival and synaptic plasticity (Poo 2001).…”
Section: Bdnf and Normal Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…ProBDNF can also inhibit neurite outgrowth and reduce spine density (Koshimizu et al 2009). In contrast, mBDNF activates the high affinity receptor, TrkB, which promotes neuronal survival and synaptic plasticity (Poo 2001).…”
Section: Bdnf and Normal Agingmentioning
confidence: 99%
“…Reduction in levels of proBDNF without a change in mBDNF could reflect increased cleavage of proBDNF as a compensatory response to preserve levels of mBDNF that promote neuronal survival and maintenance of the dendritic tree and axon (Gorski et al 2003;Matsunaga et al 2004). In contrast, proBDNF signals through the p75 NGFR and leads to neurite retraction and loss of spines (Koshimizu et al 2009), so reduced levels of proBDNF would reduce this deleterious effect. These opposite actions of the mature and pro forms of BDNF make it essential to identify the post-translational status of each form in the aging brain as total BDNF expression cannot differentiate between the state of the protein and the differences between the two signaling pathways.…”
Section: Bdnf and Normal Agingmentioning
confidence: 99%
“…According to the "Ying and Yang" hypothesis (Lu et al, 2005), both mBDNF and proBDNF have particular neurobiological properties. In particular, proBDNF regulate neuronal survival Koshimizu et al, 2009;Woo et al, 2005) and boosts synaptic pruning whereas mBDNF improves the differentiation of new neurons. Also, the conversion of proBDNF into mBDNF seems to be decisive for signal transmission and synaptic plasticity.…”
Section: The Role Of Probdnf In Patients With Schizophreniamentioning
confidence: 99%
“…Recent findings have established that mature and pro-BDNF elicit opposite biological functions Woo et al, 2005), leading to the hypothesis t h a t f r o m a n i n c o r r e c t b a l a n c i n g o f t h e d i verse isoforms may origin a pathological consequence. In recent times, Koshimizu et al (2009) pointed out that overexpression of pro-BDNF leads to apoptosis of cultured cerebellar granule neurons and produce a striking decrease in the number of cholinergic fibers of basal forebrain neurons and hippocampal dendritic spines, without disturbing the survival of these neurons. Blockade of activation of p75 receptor did not permit spine number to fall.…”
Section: The Role Of Probdnf In Patients With Schizophreniamentioning
confidence: 99%
“…proBDNF is a precursor form of BDNF. It was reported that the signaling of BDNF/TrkB and proBDNF/p75NTR promote neuronal survival and death, respectively [67,68]. There are reports showing that proBDNF may play a role in synaptic depression through p75NTR.…”
mentioning
confidence: 99%